ANALISIS DATA KESEHATAN BERBASIS GENDER NAGARI CANDUANG KOTO LAWEH KACAMATAN CANDUANG KABUPATEN AGAM - Rahmad Ramadhan; Yurni Suasti (JURNAL BUANA, 2021)
This research aims to find out gender-based public health data analysis and to map health services in Nagari Canduang Koto Laweh. The method used is Simple Random Sampling. This method is carried out by taking 4 jorong from 11 jorong out of a total of 4 jorong, 4 jorong selected based on the most population, namely Jorong Bingkudu, Jorong Lubuak Alua, Jorong Gantiang Koto Baru and Batu Balantai. Based on the Jorong that has been determined, the researchers took 30 kk per branch. Based on the results of Nagari Canduang's research, there are 15 health services such as Puskesmas, Pustu, Polindes, Pokesri, Posyandu, and the number of Pregnant Women utilizing Puskesmas in 2019 amounted to 177 people with 126 male babies and 110 female children. The number of visitors who used posyandu in the year totaled 2239 people. The coverage of B0 (0-7) / BCG immunization in infants in 2019 was 56 male and 65 female babies with a total of 121 people. Coverage of DPT-Hib Immunization, Measles 4 Polio, Complete basic immunization in infants in 2019 DPT-HB-Hib3 are 100, Polio4 is 87, Measles / MR is 64, Complete Basic Immunization is 59 people in 2019, Continued Immunization Coverage of DPT- HB-Hib 4, Measles / MR2 at the age of under two years (baduta) in 2019 amounted to 559 infants, 10 most cases of illness namely 3100 patients, Rheumatism 3411, Gastritis 3144, HT 2000 Patients, Pharinghitis 1491, Chepalgia 464, Pulp / Periapical 801, Skin Infection 695, Brochitis 405, Diabetes 263 people.